2016
DOI: 10.3390/w8120568
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Potential Health Risks of Arsenic, Selenium, and Fluorine in Natural Waters in Tibet, China

Abstract: Abstract:The contents of major and trace elements were analyzed in 204 different types of water samples in 138 villages across 51 counties and cities of Tibet. The average concentrations of arsenic (As), selenium, and fluorine for each water category decreased in the following order: arsenic (in µg/L: hot spring 241.37 > lake 27.46 > stream 22.11 > shallow well 11.57 > deep well 6. .52, 2.10, 1.68, and 1.51 µg/L in the prefectures of Shigatse, Nagchu, Lhasa, Lhoka, and Nyingchi, respectively. Carbonatite is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Rock weathering is the main factor controlling the chemical composition of the water samples ( Fig. 6), indicating that the elements in these water samples are dissolution products from the rocks and soil, which is consistent with previous studies performed in Tibet (Tian et al, 2016). Independent sample t-tests show that the concentrations of As, Ba, Ca, Cr, Hg, Mg, Ni, Se, P, Sr, SO 4 , 2and HCO 3 in drinking water exhibit significant differences between the KBD and non-KBD villages (P < 0.05).…”
Section: Differences In Drinking Water Elemental Concentrationssupporting
confidence: 91%
“…Rock weathering is the main factor controlling the chemical composition of the water samples ( Fig. 6), indicating that the elements in these water samples are dissolution products from the rocks and soil, which is consistent with previous studies performed in Tibet (Tian et al, 2016). Independent sample t-tests show that the concentrations of As, Ba, Ca, Cr, Hg, Mg, Ni, Se, P, Sr, SO 4 , 2and HCO 3 in drinking water exhibit significant differences between the KBD and non-KBD villages (P < 0.05).…”
Section: Differences In Drinking Water Elemental Concentrationssupporting
confidence: 91%
“…Wang et al reported the arsenic concentration (195 µg/L) in a dug well (groundwater) at Xungba, Tibet, arsenic levels up to 5985 µg/L in hot springs, and 10,626 µg/L in alkaline salt lakes in western Tibet [ 26 ]. In a recent study, the authors reported an average of 11.6 µg/L of arsenic in shallow wells and only 6.2 µg/L in deep wells; however, average arsenic concentrations were comparatively higher in water samples from hot springs (241.4 µg/L), lakes (27.5 µg/L), and streams (22.1 µg/L) [ 27 ]. Figure 1 shows arsenic-contaminated areas in the GRB.…”
Section: Current Magnitude Of Groundwater Arsenic Contamination Inmentioning
confidence: 99%
“…The QT is currently among the regions that are less affected by human activities and less polluted on earth. Its water environment still maintains a relatively complete native state (Tian et al, 2016). However, the special alpine environment makes the plateau ecological environment sensitive and extremely fragile.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research regarding the water chemistry on the QT has focused on the major rivers and lakes and their catchments, including Yarlung Zangbo (Sarin and Krishnaswami, 1984;Wang, 2016), Senge Zangbo (Li et al, 2012;Wang et al, 2012), Three River Resource areas (Deng, 1988;Wu et al, 2008;Cao, 2013;Tan et al, 2016), Qinghai Lake (Hou et al, 2009;Jin et al, 2009;Xiao et al, 2012), Yamzhog Yumco Zhang et al, 2012;Sun et al, 2013;Zhe et al, 2017), Pumayum Co (Ju et al, 2010;Zhu et al, 2010), Nam Co (Gao et al, 2008;Wang et al, 2013), Mapam Yumco (Yao et al, 2015). Some scholars have also studied water chemistry in some areas of the QT (Zhang and Gustafsson, 1995;Guo and Wang, 2012;Tian et al, 2015), including microorganisms (Nie, 2011;Zhang et al, 2013;Zhao et al, 2017), heavy metals and trace elements (Cao et al, 2000;Grange et al, 2001;Li et al, 2006;Sheng et al, 2012;Tian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%